Dietary Supplementation of Bile Acids in Tongue Sole (Cynoglossus semilaevis): A Promising Strategy to Improve Hepatic Health Status - Wang, Shengpeng; Zhang, Wei; Cao, Aizhi; Pan, Zhongchao; Liu, Tailiang (Frontiers in Marine Science, 2022)
A 10-week feeding trial was conducted to investigate the beneficial effects of bile acids (BAs) on hepatic health status in tongue sole (Cynoglossus semilaevis). Three experimental diets were prepared with different levels of BA inclusion in the commercial basal diet: control group (CT: 0 mg/kg basal diet), low-level group (BA1: 300 mg/kg basal diet), and high-level group (900 mg/kg basal diet). At the end of the feeding trial, growth performance and survival rate were measured, as well as numerous physiological and biochemical parameters of the liver, including four hepatic function indices, five antioxidant indices, five lipid metabolism parameters, and three digestive enzyme activities. Moreover, the mRNA expression levels of three growth-related genes and three immune-related genes in the liver were assayed. Results showed that growth performance and survival were substantially improved in both low- and high-level BA inclusive groups. Further, the tested liver physiological and biochemical parameters combined with the quantitative real-time PCR results revealed enhanced antioxidant capacity, energy metabolism, digestive ability, and immune response. Finally, these findings provide a wider spectrum of the beneficial effects of dietary BAs on liver health in tongue sole.